PENGARUH KEPEMIMPINAN, PUNISHMENT, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI RIAU - Ulia May Zafirah; Marzolina Marzolina; Rosnelly Roesdi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research was to analyze the influence of leadership, punishment and organizational culture simultaneously on employee performance of Department Energy and Mineral Resources Riau Province, as 66 employees.Primary data was collected by questionnaires as instrument to prove the result of research, to test the hypothesis in this research is to use multiple linear regresion analysis with the help of SPSS. The sampling technique that has been selected is a simple random sampling method. he result of the research shows that: 1) There are positive and significant influence of leadership on the employees performance of the Department of Energy and Mineral Resources of Riau Province; 2) there is a negative and significant effect of punishment on the employees performance of the Department of Energy and Mineral Resources of Riau Province; 3) positive and significant influence of organizational culture on the performance of employees of the Department of Energy and Mineral Resources Riau Province, 4) leadership, punishment, and organizational culture simultaneously have a significant effect on the employees performance of Department of Energy and Mineral Resources Riau ProvinceKeywords : Employee Performance, Leadership, Punishment, Organizational Culture